Continuous narcotic infusions for relief of postoperative pain. - Church, J J (1979)
Relief of acute pain after surgery or trauma is still inadequate in many centres, most patients being treated with intermittent intramuscular injections of narcotic analgesics. Over the past three years continuous intravenous narcotic infusions have been used at this hospital to treat postoperative pain; recently a system has been devised whereby an hourly dose is given and the dispenser recharged every hour. The method used is cheap and reliable, and signs of overdosage may be easily checked by nursing staff. Side effects rarely occur. Fifty patients who had received intravenous infusions after undergoing major abdominal surgery were sent a questionnaire to assess postoperative pain, and the results were compared with those from 50 matched controls who had received intramuscular injections. Of those who replied, only four patients who had received the infusion had found the pain distressing compared with 13 controls. Continuous narcotic infusions are most effective in relieving postoperative pain and may be given cheaply and reliably.